Nanotechnology Approach for Exploring the Enhanced Bioactivities and Biochemical Characterization of Freshly Prepared Nigella sativa L. Nanosuspensions and Their Phytochemical Profile - Ali, Tayyab; Hussain, Fatma; Naeem, Muhammad; Khan, Ajmal; Al-Harrasi, Ahmed (Frontiers in Bioengineering and Biotechnology, 2022)
Nigella sativa is one of the most commonly used medicinal plant as it exhibits several pharmacological activities like antioxidant, antibacterial, anticancer, antidiabetic and hemolytic. The purpose of this study aims to apply the nanotechnology approach for exploring the enhanced bioactivities of freshly prepared Nigella sativa L nanosuspensions and phytochemical profile of N. sativa seeds ethanolic extract. In this study, we performed biochemical characterization of Nigella sativa L ethanolic extract through High-Pressure Liquid Chromatography (HPLC), Fourier Transform Infrared Spectroscopy (FT-IR), Gass Chromatography (GC) and bioactivities in terms of antioxidant, antidiabetic, antibacterial and hemolytic activities of nanosuspension and extract were competitively studied. Results revealed that the nanosuspension of N. sativa seeds showed higher total phenolic (478.63± 5.00 mg GAE/100 g) and total flavonoid contents (192.23± 1.390 mg CE/100 g) as compared to ethanolic seeds extract. The antioxidant activity was performed by DPPH scavenging assay; nanosuspension showed higher potential (16.74± 1.88 %) as compared to extract. The antidiabetic activity was performed by antiglycation and α- amylase inhibition assays, nanosuspension showed higher antidiabetic potential (antiglycation (58±0.912%)) and (bacterial α- amylase inhibition (18.0 ± 1.3675 %) respectively. Nanosuspension showed higher biofilm inhibition activity against Escherichia coli (66.44± 3.529 %) as compared to extract (44.96± 2.238 %) and ciprofloxacin (59.39± 3.013%). Hemolytic activity was performed and nanosuspension showed higher hemolytic activity as compared to extract as 7.8 ± 0.1% and 6.5 ± 0.3%, respectively. The study showed that nanosuspension had enhanced the bioavailability of bioactive plant compounds as compared to ethanolic extract. So, nanosuspension of N. sativa seeds extract showed higher biochemical activities as compared to ethanolic extract. This nanotechnology approach can be used as platform for the development of combination protocols for the characterization of liquid state nanosuspensions in an adequate manner and also for therapeutic applications.